2019
DOI: 10.11152/mu-1976
|View full text |Cite
|
Sign up to set email alerts
|

Elastosonographic evaluation after extracorporeal shockwave treatment in plantar fasciopathy

Abstract: Aim: To assess the ultrasound features in patients with plantar fasciopathy before and after extracorporeal shock waves therapy (ESWT), using conventional grey-scale imaging and both strain (SE) and shear wave (SWE) elastosonographic evaluation.Material and method: Consecutive patients of both sexes attending our outpatient’s clinic, with diagnosis of unilateral plantar fasciopathy, were enrolled. Patients were treated with 3 sessions of ESWT once a week, and underwent clinical and ultrasound evaluation at bas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 39 publications
1
9
0
Order By: Relevance
“…In this study, we recorded results consistent with the literature for the application of ESWT in the medial insertion of plantar fascia 50 . We achieved similar to better results in terms of foot pain, disability and time needed for recovery with the release of proximal myofascial points using the fascial manipulation method.…”
Section: Discussionsupporting
confidence: 86%
“…In this study, we recorded results consistent with the literature for the application of ESWT in the medial insertion of plantar fascia 50 . We achieved similar to better results in terms of foot pain, disability and time needed for recovery with the release of proximal myofascial points using the fascial manipulation method.…”
Section: Discussionsupporting
confidence: 86%
“…This is the first research to show the efficacy of ESWT on the structural properties of AT. Altivi et al[ 14 ] reported that the thickness and stiffness of plantar fascia increased with three sessions of ESWT in patients with plantar fasciopathy. Additional studies are needed to investigate the relationship between ESWT and tendon stiffness.…”
Section: Discussionmentioning
confidence: 99%
“…[ 13 ] Many studies have investigated the relationship between EE and tendon structure; however, the number of studies investigating tendon structure following ESWT is limited. [ 14 ] In preclinical studies, increased vascularization was reported in the bone-tendon junction with the use of ESWT; however, tendon neovascularization with ESWT has not been demonstrated in clinical studies. [ 15 , 16 ] To our knowledge, there is no clinical trial examining the efficacy of ESWT on tendon thickness and stiffness in midportion AT.…”
Section: Introductionmentioning
confidence: 99%
“…[16][17][18][19][20] Shear wave elastography (SWE), a recently developed, noninvasive ultrasound (US) imaging technique, has been used to assess the mechanical properties of muscles and tendons. [21][22][23][24][25][26][27][28] It provides information on tissue elasticity and stiffness by using an impulse generated by the transducer with the shear wave propagating at a higher speed in stiffer tissues 29 and seems to be able to detect modifications of tissue elasticity earlier than conventional B-mode US. 30,31 The aim of our study was to evaluate the characteristics of the medial gastrocnemius MTJ with SWE in a resting position and during muscle contraction in healthy people.…”
mentioning
confidence: 99%
“…The evaluation of the muscle‐tendon unit stiffness has been studied thoroughly in the literature by different methods . Shear wave elastography (SWE), a recently developed, noninvasive ultrasound (US) imaging technique, has been used to assess the mechanical properties of muscles and tendons . It provides information on tissue elasticity and stiffness by using an impulse generated by the transducer with the shear wave propagating at a higher speed in stiffer tissues and seems to be able to detect modifications of tissue elasticity earlier than conventional B‐mode US .…”
mentioning
confidence: 99%